2005
DOI: 10.1208/pt060240
|View full text |Cite
|
Sign up to set email alerts
|

Lecithin organogels as a potential phospholipid-structured system for topical drug delivery: A review

Abstract: The purpose of this review is to give an insight into the considerable potential of lecithin organogels (LOs) in the applications meant for topical drug delivery. LOs are clear, thermodynamically stable, viscoelastic, and biocompatible jelly-like phases, chiefly composed of hydrated phospholipids and appropriate organic liquid. These systems are currently of interest to the pharmaceutical scientist because of their structural and functional benefits. Several therapeutic agents have been formulated as LOs for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
141
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(151 citation statements)
references
References 75 publications
(113 reference statements)
1
141
0
3
Order By: Relevance
“…Pluronic lecithin organogel (PLO) is a very interesting system, owing to their biocompatibility, their amphiphilic nature, facilitating dissolution of various drug classes, as well as their permeation enhancement properties. A number of studies have shown that pluronic lecithin organogel have the unique capacity to deliver the drugs through the skin and particular medications such as NSAIDs, hormones, anti-emetics, opoids, anti-psychotic drugs, calcium channel blockers, and local anesthetics to a specific site when other routes of administration are not viable (Kumar & Katare, 2005;Murdan, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Pluronic lecithin organogel (PLO) is a very interesting system, owing to their biocompatibility, their amphiphilic nature, facilitating dissolution of various drug classes, as well as their permeation enhancement properties. A number of studies have shown that pluronic lecithin organogel have the unique capacity to deliver the drugs through the skin and particular medications such as NSAIDs, hormones, anti-emetics, opoids, anti-psychotic drugs, calcium channel blockers, and local anesthetics to a specific site when other routes of administration are not viable (Kumar & Katare, 2005;Murdan, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Lecithin is used as a nutritional supplement and thought to protect cells from oxidation, prevent cardiovascular disease and steatosis (2)(3)(4)(5)(6). It was also used in phospholipidstructured system for topical drug delivery (7). A study showed that the components of lecithin, such as oleic, palmitic and linoleic acid, activates peroxisome proliferator-activated receptor Á (PPARÁ) (8).…”
Section: Introductionmentioning
confidence: 99%
“…However, the addition of small and critical quantities of a polar solvent induces an aggressive uniaxial growth of spherical micelles into tubular or cylindrical micellar aggregates ( Fig. 2) (36). The binding of the polar molecules in stoichiometric ratios to the hydrophilic head of lecithin molecules results in the formation of a linear framework, where two adjacent lecithin molecules are linked by a polar molecule (36)(37)(38).…”
Section: Mechanism Of Organogelationmentioning
confidence: 99%
“…2) (36). The binding of the polar molecules in stoichiometric ratios to the hydrophilic head of lecithin molecules results in the formation of a linear framework, where two adjacent lecithin molecules are linked by a polar molecule (36)(37)(38). This linear framework is a result of hydrogen bonds formed by polar molecules and the phosphate group of lecithin molecules.…”
Section: Mechanism Of Organogelationmentioning
confidence: 99%